2023
DOI: 10.1021/acs.orglett.3c00870
|View full text |Cite
|
Sign up to set email alerts
|

Bisazapentalene Dication: Global Aromaticity and Open-Shell Singlet Ground State

Abstract: Antiaromatic moieties fused in polycyclic π-conjugated molecules usually exhibit strong localized antiaromaticiy. Herein, we reported the synthesis and properties of a bisazapentalene dication (BAP 2+ ) obtained from in situ two-electron oxidation of neutral species 8. Noteworthily, it possesses global aromaticity and an open-shell singlet ground state. This study underlines the importance of heteroatoms in determining the delocalization of π-electrons and the aromaticity of molecules in their oxidized states. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In summary, carbazole-, dibenzothiophene-, dibenzofuran-, and dibenzo[ b , d ]thiophene-5,5-dioxide-fused s -indacene antiaromatics 1 – 4 , respectively, were synthesized and characterized to show the tunable paratropicity of the s -indacene unit. The design of 1 – 4 is unlike the earlier reports, where the larger double-bond character of five-membered heteroles (pyrrole, furan, thiophene) was readily utilized by annealing with the s -indacene unit to enhance its paratropic ring-current strength by enhancing the BLA. Based on experimental 1 H NMR spectral analyses, 4 was found to show the weakest antiaromatic character of the s -indacene unit, while 3 showed moderate antiaromaticity, and a relatively enhanced antiaromaticity for 2 and 1 was documented.…”
Section: Discussionmentioning
confidence: 97%
“…In summary, carbazole-, dibenzothiophene-, dibenzofuran-, and dibenzo[ b , d ]thiophene-5,5-dioxide-fused s -indacene antiaromatics 1 – 4 , respectively, were synthesized and characterized to show the tunable paratropicity of the s -indacene unit. The design of 1 – 4 is unlike the earlier reports, where the larger double-bond character of five-membered heteroles (pyrrole, furan, thiophene) was readily utilized by annealing with the s -indacene unit to enhance its paratropic ring-current strength by enhancing the BLA. Based on experimental 1 H NMR spectral analyses, 4 was found to show the weakest antiaromatic character of the s -indacene unit, while 3 showed moderate antiaromaticity, and a relatively enhanced antiaromaticity for 2 and 1 was documented.…”
Section: Discussionmentioning
confidence: 97%
“…[25] Molecular structures were fully optimized without imposing symmetry constraints by DFT computations at the B3LYP/aug-cc-pVTZ level. [26] The good performance of the B3LYP functional in benchmark studies justifies its extensive use and several recent reports confirm its reliability in aromaticity related applications on ground and excited states (see for example References [2,3,5,6,10,11,15,16,21,24] and references therein). The restricted and unrestricted procedures were applied for singlet and triplet electronic states respectively.…”
Section: Computational Methodologymentioning
confidence: 99%
“…However, a very recent study indicated that the presence of heteroatoms is crucial in determining the delocalization of π-electrons and the aromaticity of the oxidized species. [24] The aim of this work was to further examine the scope of aromaticity/antiaromaticity in polycyclic π-conjugated molecules, and to provide a better understanding of the electron delocalization behavior of the diionic compounds. In this context, several computed features of the charged species were compared with those of the corresponding neutral parent aromatic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation